INFLUENCE OF MAGNETIC AND ELECTRIC GRINDING PARAMETERS ON HARDNESS, WEAR-RESISTANCE AND CHEMICAL COMPOSITION OF PROTECTIVE GAS AND THERMAL COATINGS - N. V. Spiridonov; M. V. Neroda; I. O. Sokorov (Наука и техника)
The paper investigates influence of magnetic and electric grinding parameters on formation of physical and mechanical properties of protective coatings. It has been established that it is possible to control chemical composition, properties and qualitative characteristics of hardening coatings while changing technological process parameters.